DNA methylation in candidate genes for handedness predicts handedness direction. Issue 4 (4th July 2018) - Schmitz, Judith; Kumsta, Robert; Moser, Dirk; Güntürkün, Onur; Ocklenburg, Sebastian
ABSTRACT: Handedness is a complex trait influenced by both genetic and non-genetic factors. Asymmetries of DNA methylation and gene expression in the developing foetus are thought to underlie its development. However, its molecular epigenetics are not well understood. We collected buccal cells from adult left- and right-handers ( n  = 60) to investigate whether epigenetic biomarkers of handedness can be identified in non-neuronal tissue. We associated DNA methylation in promoter regions of candidate genes with handedness direction. Results indicate that DNA methylation of genes asymmetrically expressed in the foetal brain or spinal cord might play a role within such a multifactorial model. Moreover, we provide tentative evidence that birth stress might be a factor that affects DNA methylation in NEUROD6, a gene that is asymmetrically expressed in foetal brains.